33.1k views
4 votes
Can you help me with the answer please ? I would be so thank with u

Can you help me with the answer please ? I would be so thank with u-example-1
Can you help me with the answer please ? I would be so thank with u-example-1
Can you help me with the answer please ? I would be so thank with u-example-2

1 Answer

7 votes

Answer:

  • exponent of p: 3
  • exponent of q: 2

Explanation:

The applicable rule is ...


(a^b)/(a^c)=a^(b-c)

For p:


(p^5)/(p^2)=p^(5-2)=p^3

The exponent of p is 3.

For q:


(q^4)/(q^2)=q^(4-2)=q^2

The exponent of q is 2.

User Animesh Kumar Paul
by
5.4k points